Proposal of a Biomechanical Model of the Chest Technique in Soccer Volleyball; [Propuesta de Un Modelo Biomecánico de la Técnica de Pecho en Futvoley] - Aedo-Munoz, E; Arriagada-Tarifeno, D; Merino-Munoz, P; Brito, C (Federacion Espanola de Docentes de Educacion Fisica, 2024)
Context: The biomechanical analysis of sports techniques facilitates performance optimization, promotes proper technical execution, and helps to identify injury risk factors. Objective: To propose a biomechanical model of the chest technique in footvolley, indicating kinematic indicators for its evaluation. Methods: A case study with a descriptive scope was conducted through a participant with 20 years of experience in footvolley. The chest technique in footvolley was captured through video-photogrammetry using a high-speed camera (240 Hz). The analysis was carried out using the Kinovea® sports analysis software. The phases of the sports technique were determined through a previously used proposal: a) The general performance objective of the technique (GPO); b) The mechanical purposes (MP) of each phase, which refers to the main mechanical characteristic to be achieved in each phase; c) Biomechanical objec-tives (BO), corresponding to the kinematic (KI) and kinetic indicators (KnI) derived from the MP. Results: The technique was divided into the phases of Approach, Preparation, Impulse, and Follow-up. In each phase, the GPO of the technique and the MPs and BOs were described. Practical applications: The biomechanical proposal based on GPO, MP, and KI allows for the understanding of this sports technique, facilitating its analysis, teaching, and performance optimization. © 2024 Federacion Espanola de Docentes de Educacion Fisica. All rights reserved.